Safety of major reconstructive surgery during the peak of the COVID-19 pandemic in the United Kingdom and Ireland – multicentre national cohort study. Issue 6 (June 2021) - Patel, N.G.; Reissis, D.; Mair, M.; Hart, A.; Ragbir, M.; Giele, H.; Mosahebi, A.; Ramakrishnan, V.; ,
Summary: Background: The safety of surgery during and after the coronavirus disease-2019 (COVID-19) pandemic is paramount. Early reports of excessive perioperative mortality in COVID-positive patients promoted the widespread avoidance of operations. However, cancelling or delaying operations for cancer, trauma, or functional restitution has resulted in increased morbidity and mortality. Methods: A national multicentre cohort study of all major reconstructive operations carried out over a 12-week period of the 'COVID-19 surge' in the United Kingdom and Ireland was performed. Primary outcome was 30-day mortality and secondary outcome measures were major complications (Clavien-Dindo grade ≥3) and COVID-19 status of patients and healthcare professionals before and after surgery. Results: A total of 418 patients underwent major reconstructive surgery with a mean operating time of 7.5 hours and 12 days' inpatient stay. Cancer (59.8%) and trauma (29.4%) were the most common indications. COVID-19 infection was present in 4.5% of patients. The 30-day post-operative mortality was 0.2%, reflecting the death of one patient who was COVID-negative. Overall complication rate was 20.8%. COVID status did not correlate with major or minor complications. Eight healthcare professionals developed post-operative COVID-19 infection, seven of which occurred within the first three weeks. Conclusions: Major reconstructive operations performed during the COVID-19 crisis have been mostly urgent cases involving all surgical specialties. This cohort is a surrogate for all major operations across all surgical specialties. Patient safety and surgical outcomes have been the same as in the pre-COVID era. With adequate precautions, major reconstructive surgery is safe for patients and staff. This study helps counsel patients of COVID-19 risks in the perioperative period.